A STUDY OF ENGLISH INTONATION IN INDONESIAN EFL LEARNERS - Roni Nursyamsu; Lukluk Argita Munif (University of Kuningan, 2013)
Abstract: This study examined the patterns of intonation and kinds of information structure that occur in EFL learners. The objectives of this study were: (1) to know the patterns of intonation that occur in EFL learners; (2) to know kinds of information structure that occur in EFL learners. The method used in this study is descriptive qualitative and the subjects of this study is a debater and also a student in English Department at one of private university in Kuningan, West Java. Techniques of collecting data used in this research were library research, observation and interview. Halliday’s theory and PRAAT Software Analysis use in this research to analyze the data. Based on the data analysis, it can be known that: (1) There were 5 kinds of intonation pattern used by the speaker: fall, rise (final), rise (non-final), fall-rise (final), fall-rise (non-final); (2) There were 158 clauses with 25 independent clauses and 133 dependent clauses from the respondent’s performance; (3) There were three systems from information structure: tonality, tonicity, and tone; (4) In tonality system, H-TS-T with the percentage 18% was the most pattern used by the respondent; (5) Given-New-Given (G-N-G) with the precentage 36% was mostly used in her performance based on tonicity system; (6) Incomplete information (rise non-final) was the most dominant intonation pattern used by the respondent with the precentage 33%.Keywords: intonation, information structure, EFL learners